2009
DOI: 10.2174/138161209789057986
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase: An Important Mediator of Atherosclerosis and Vascular Disease

Abstract: Atherosclerosis is a complex inflammatory process characterized by the cross-talk between excessive inflammation and lipid accumulation. In the past few years, compelling evidence suggests that statins can decrease vascular inflammation and attenuate the development of atherosclerosis through their so-called "pleiotropic effects". These cholesterol-independent effects are predominantly due to their ability to inhibit isoprenoid synthesis. In particular, inhibition of geranylgeranylpyrophosphate synthesis leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 97 publications
3
73
0
Order By: Relevance
“…26 Coincident with these finding, our data revealed that knockdown of RhoA was capable of increasing p53 protein levels and inhibiting VEGF expression, but the inhibition of VEGF mediated by siRhoA was abolished after p53 knockdown.…”
Section: Discussionsupporting
confidence: 79%
“…26 Coincident with these finding, our data revealed that knockdown of RhoA was capable of increasing p53 protein levels and inhibiting VEGF expression, but the inhibition of VEGF mediated by siRhoA was abolished after p53 knockdown.…”
Section: Discussionsupporting
confidence: 79%
“…Using a cell culture model, we reproduced the report that KCl stimulates myocardin mRNA expression and the expression of its target genes through the RhoA-ROCK pathway in vascular SMCs. 11 Because ATV is well known to inhibit the RhoA-ROCK pathway in various cell types, including vascular SMCs, 23 our observation that ATV inhibits KCl- induced myocardin expression has further substantiated a novel mechanism underlying direct inhibition of vessel contractility by ATV or other statins. Finally, our results showing inhibition of RhoA activation and membrane translocation by ATV and its prevention by Meva further support the involvement of the RhoA-ROCK pathway.…”
Section: Discussionmentioning
confidence: 79%
“…Excessive RhoA/Rhokinase activity may lead to a decrease in NO synthesis and to endothelial dysfunction and RhoA/Rhokinase inhibitors to reverse this have made RhoA/Rhokinase pathway an important therapeutic target in cardiovascular treatment [38].…”
Section: Discussionmentioning
confidence: 99%